Prevalence and antimicrobial resistance of three clones (ST1223, ST2198, ST2250) of Staphylococcus argenteus clinical isolates in northern Japan - Meiji Soe Aung; Noriko Urushibara; Mitsuyo Kawaguchiya; Nobuhide Ohashi; Mina Hirose; Kenji Kudo; Masahiko Ito; Nobumichi Kobayashi (Journal of Global Antimicrobial Resistance)
Objectives: Staphylococcus argenteus, a newly described species of coagulase-positive Staphylococcus, was first identified in clinical isolates in northern Japan in 2019. The aim of the present study was to clarify the trends in the epidemiological features and antimicrobial resistance traits of S. argenteus in the recent years. Methods: S. argenteus isolates from various clinical specimens were screened using MALDI-TOF and genotyped using the multilocus sequence typing scheme. Antimicrobial susceptibility was determined using broth microdilution test and resistance genes were detected by multiplex/uniplex PCR. Nucleotide sequences of haemolysin genes (hla, hlb, hld, and hlg) were determined and analysed in some isolates. Results: From August 2020 to December 2023, 210 isolates were identified as S. argenteus. The ratio of S. argenteus to Staphylococcus aureus clinical isolates was 0.0045, showing a slightly decreasing trend compared to what was previously reported (2019.8–2020.7). Three genotypes, ST1223-coa-XV, ST2198-coa-XIV, and ST2250-coa-XId were identified, with ST2250 being dominant (49%) and exhibiting an increasing trend. S. argenteus isolates were almost susceptible to antimicrobials examined, while ST2198 isolates showed higher resistance rates to ampicillin, macrolides, and aminoglycosides than other clones, harbouring blaZ, msrA, and aac(6′)-Ie-aph(2″)-Ia. Only eight isolates (4-ST2250, 3-ST1223, and 1-ST2198) did not show haemolysis on blood agar plates. These isolates had intact haemolysin genes and promoter regions; however, a novel deletion mutation in hlg-component A was detected in some haemolytic and non-haemolytic isolates. Conclusions: The present study revealed the epidemiological trend of S. argenteus clones in northern Japan, along with the occurrence of non-haemolytic isolates with intact haemolysin genes.